OPTIMIZATION OF PETROLEUM HYDROCARBON CONTAMINATED SOIL RECOVERY USING ELECTROKINETIC TECHNIQUE - SURYA RAMADAN ( NIM: 25315030 ), BIMASTYAJI
Soil contamination around petroleum exploration field may damage the ecosystem and endanger the human life so that a treatment strategy is required if such contamination has occurred. Electrokinetic remediation is an alternative to contaminated soil-processing technology that lowering its investment cost and is able to improve the bioremediation process. In this research, there are 3 parameters which become independent variable: time, surfactant concentration and electrode distance with the same voltage gradient that is 1 V / cm. The surfactant used was tween 80 with the critical micelle concentration value (CMC) of 2; 4; 6 and 8 CMC. The reactor length used varies from 12; 18 and 30 cm. From the biodegradation test, tween 80 can be degraded by a consortium of microorganisms where the concentration of 6 CMC is faster degraded than the other concentration levels. The feasibility test is used to determine the environmental control variable. The results show that electrochemical process is able to keep the water content in the range of 24-30%, increase the temperature from 0.5 to 1 ° C, and keep the pH in the range of 4-5. The biggest efficiencty of Total Petroleum Hydrocarbon (TPH) degradation occurred at the concentration of surfactant 6 CMC and electrode distance of 18 cm that is equal to 49,94% and 44,36%. In 6 CMC variation, TPH concentration decrease from 3,93% to 1,97%, meanwhile in 18 cm of electrode distance, TPH concentration decrease from 3,79% to 2,11%. The average number of colonies of microorganisms almost decreased in all treatments on the third day, whereas for reactors with 6 CMC of surfactant concentrations, the total number of colonies of microorganisms decreased from ± 4,98 x 107 CFU/ml to 5,77 x 106 CFU/ml. The largest number of colonies of microorganisms on the last day for the variation of surfactant concentration was controlled reactor with the number of microorganisms of 1,435 x 107 CFU/ml while for the electrode distance variation, the largest number of microorganisms was in the 30 cm reactor at 1,448 x 107 CFU/ml.